Potencial de Bacillus subtilis en la autorreparación de concreto fisurado: Evaluación de la bioprecipitación de carbonato de calcio - Alhuay Coaguila, Dana Alessandra; Silva Ipanaque, Jose Hugo; Vargas Chang, Esther Joni; Yupanqui Apolinario, Eduardo; Rodriguez Carrillo, Sol Angel; Gonzales Rivasplata, José Miguel (LACCEI, 2025)
The present study aims to evaluate the potential of the bacterium Bacillus subtilis for the self-repair of cracked concrete (concrete with compressive strength of 210 kg/cm²) by the process of calcium carbonate bioprecipitation. Microbiological and physicochemical evaluations of the bacterial strain used were carried out, as well as quality control of the construction materials, specifically fine and coarse aggregates, for the design of the concrete mix. In the laboratory, the bacterium Bacillus subtilis was characterized under different pH. Mechanical compression and bending tests were performed on cylindrical, prismatic and cubic specimens, to evaluate the effectiveness of the repair system based on the mechanical properties and self-healing capacity of the concrete. The results showed that calcium carbonate bioprecipitation allowed the repair of fissures up to 0.15 mm wide in a period of 7 days. In conclusion, calcium carbonate bioprecipitation mediated by Bacillus subtilis is presented as an effective alternative for the self-repair of fissures in concrete f'c 210 kg/cm², especially in alkaline conditions, which makes it a possible solution for urban and industrial structures.